Giemsa-stained wet mount based method for reticulocyte quantification: a viable alternative in resource limited or malaria endemic settings - Lee, W; Russell, B; Lau, Y; Fong, M; Chu, C; Sriprawat, K; Suwanarusk, R; Nosten, F; Renia, L (Public Library of Science, 2013)
The quantity of circulating reticulocytes is an important indicator of erythropoietic activity in response to a wide range of haematological pathologies. While most modern laboratories use flow cytometry to quantify reticulocytes, most field laboratories still rely on ‘subvital’ staining. The specialist ‘subvital’ stains, New Methylene Blue (NMB) and Brilliant Crésyl Blue are often difficult to procure, toxic, and show inconsistencies between batches. Here we demonstrate the utility of Giemsa's stain (commonly used microbiology and parasitology) in a ‘subvital’ manner to provide an accurate method to visualize and count reticulocytes in blood samples from normal and malaria-infected individuals.